2023
DOI: 10.1186/s12888-022-04483-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of outpatient and community treatments for people with a diagnosis of ‘personality disorder’: systematic review and meta-analysis

Abstract: Background Quality of care and access to effective interventions have been widely criticised as limited for people diagnosed with ‘personality disorder’ or who have comparable needs (described in some recent papers as “Complex Emotional Needs” (CEN). It is important to identify effective interventions and the optimal context and mode of delivery for people with CEN. We aimed to investigate the effectiveness of psychosocial interventions delivered in community and outpatient settings in treating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…We did not find significant associations between these variables, however, more research is needed with larger samples. Current evidence supports several psychological interventions such as, schema therapy, psychodynamic and mentalisation based approaches as efficacious in treating BPD symptoms (Katakis et al, 2023 ). It is plausible these alternative treatments related to both length and theoretical orientation may expect similar findings.…”
Section: Discussionmentioning
confidence: 96%
“…We did not find significant associations between these variables, however, more research is needed with larger samples. Current evidence supports several psychological interventions such as, schema therapy, psychodynamic and mentalisation based approaches as efficacious in treating BPD symptoms (Katakis et al, 2023 ). It is plausible these alternative treatments related to both length and theoretical orientation may expect similar findings.…”
Section: Discussionmentioning
confidence: 96%
“…None of the trials focused exclusively on NPD patients. Further meta-analyses reviewing the efficacy of long-term psychodynamic therapy (PDT) [31] and psychological treatments in general [32][33][34] also found a lack of scientifically sound studies looking at treatment efficacy for NPD. Even though the limited number of studies prevented the formation of solid conclusions on treatment efficacy for NPD, the authors found that significant progress has been made in this research area, with an increasing number of RCTs conducted over the previous decade.…”
Section: Introductionmentioning
confidence: 99%